Sex Hormones Enhance Gingival Inflammation without Affecting IL-1β and TNF-α in Periodontally Healthy Women during Pregnancy - Min Wu; Shao-Wu Chen; Wei-Lan Su; Hong-Ying Zhu; Shu-Yuan Ouyang; Ya-Ting Cao; Shao-Yun Jiang (Hindawi Limited, 2016)
Hormones (progesterone and estradiol) change greatly during pregnancy; however, the mechanism of hormonal changes on gingival inflammation is still unclear. This study is to evaluate the effects of hormonal changes during pregnancy on gingival inflammation and interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in gingival crevicular fluid (GCF). 30 periodontally healthy pregnant women were evaluated in the first, second, and third trimesters. 20 periodontally healthy nonpregnant women were evaluated twice (once per subsequent month). Clinical parameters including probing pocket depth (PPD), bleeding index (BI), gingival index (GI), clinical attachment level (CAL), and plaque index (PLI) were recorded. GCF levels of IL-1β and TNF-α and serum levels of progesterone and estradiol were measured. From the data, despite low PLI, BI and GI increased significantly during pregnancy; however, no significant changes in PLI, CAL, IL-1β, or TNF-α GCF levels were observed. Although IL-1β, not TNF-α, was higher in pregnant group than in nonpregnant group, they showed no correlation with serum hormone levels during pregnancy. GI and BI showed significant positive correlation with serum hormone levels during pregnancy. This study suggests that sex hormone increase during pregnancy might have an effect on inflammatory status of gingiva, independent of IL-1β and TNF-α in GCF.